24‐3: Complementary LTPO Technology, Pixel Circuits and Integrated Gate Drivers for AMOLED Displays Supporting Variable Refresh Rates. Issue 1 (25th September 2020) - Luo, Haojun; Wang, Shaowen; Kang, Jiahao; Wang, Yu‐Min; Zhao, Jigang; Tsong, Tina; Lu, Ping; Gupta, Amit; Hu, Wenbing; Wu, Huanda; Zhang, Shengwu; Kim, Jiha; et al.
Abstract : A Complementary Low‐temperature Poly‐Crystalline Silicon and Oxide (LTPO) technology based on p‐type Low‐temperature Poly‐Crystalline Silicon (LTPS) and n‐type oxide Thin‐Film Transistors (TFTs) was developed and demonstrated. New pixel circuits and Gate‐on‐Array (GOA) circuits were designed and fabricated using this technology. By combining the superior driving capability of LTPS and ultra‐low leakage of oxide semiconductor, all the pixel circuits and GOA circuits can operate between 1 Hz and 120 Hz, which enables both high refresh rate and low standby power display applications.